BIODEGRADATION DYE INDIGOSOL GOLDEN YELLOW IRC USING VERTICAL BIOSYSTEM - Sophia Maria Oliva Lau; I Wayan Budiarsa Suyasa; James Sibarani (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2018)
The artificial waste of indigosol golden yellow irc dye has been processed using vertical biosystems with dimension of 30cm x 30 cm x 37 cm in the presence of Typha angustifolia Linnaeus plant and the addition of active mud seed from Batanta island road. The artificial wastes of indigosol golden yellow irc dye are made with concentrations of 25 mg / L. The processing of dye indigosol golden yellow irc is done by immersion system for 0, 1, 2, 3, until 4 days. Reduced concentration of indigosol golden yellow irc dye was measured using a uv-vis spectrophotometer and also measured the reduced concentration of COD, TDS and TSS. The results show vertical biosystem able to degrade The artificial waste of indigosol golden yellow irc dye, COD, TDS, and TSS are 47,80%; 41.17%; 76.51% and 63.06%. Keywords: Vertical Biosystems, Typha angustifolia Linnaeus, indigosol golden yellow irc